2007
DOI: 10.1097/wnr.0b013e3282f0b542
|View full text |Cite
|
Sign up to set email alerts
|

The expression and distribution of neural salient serine/arginine-rich protein 1 in rat retina

Abstract: Neural salient serine/arginine-rich protein 1 (NSSR1) expression has been found in mouse cerebral neurons, cerebellar Purkinje cells, pyramidal neurons and granule cells of dentate gyrus and regulates the pre-mRNA splicing of genes important for neural functions. In this study, we demonstrated that NSSR1 is expressed in rat retina and extensively distributed in the outer and inner plexiform layers. Double staining experiments showed that NSSR1 distributed mainly in ON-type bipolar cells and localized in the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Neural salient serine/ arginine-rich protein (NSSR, also named SRp38) is a newly characterized SR protein originally cloned in the human leukemia cell lines and therefore called translocation liposarcoma (TLS)-associated serine-arginine proteins and has two isoforms (NSSR1 and NSSR2) [4,5]. It is predominantly expressed in neural tissues such as cerebral neurons, cerebellar Purkinje cells, and retinal bipolar cells, and plays important roles in regulating neural differentiation and neural-specific alternative splicing [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Neural salient serine/ arginine-rich protein (NSSR, also named SRp38) is a newly characterized SR protein originally cloned in the human leukemia cell lines and therefore called translocation liposarcoma (TLS)-associated serine-arginine proteins and has two isoforms (NSSR1 and NSSR2) [4,5]. It is predominantly expressed in neural tissues such as cerebral neurons, cerebellar Purkinje cells, and retinal bipolar cells, and plays important roles in regulating neural differentiation and neural-specific alternative splicing [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Sperm cells were fixed 4% PFA on glass slide and air dried at room temperature, and then treated with MeOH at −20°C for 30 min. Immunofluorescent labeling was performed following the standard method with rabbit anti-NSSR1 antiserum as primary antibodies and FITC-labeled goat anti-rabbit IgG as secondary antibodies [16]. The specificity of anti-NSSR1 antibodies has been demonstrated previously [17].…”
Section: Methodsmentioning
confidence: 99%
“…NSSR1 is predominantly expressed in neural tissues such as cerebral neurons, cerebellar Purkinje cells and retinal bipolar cells, and plays important roles in regulating neural differentiation and neural-specific alternative splicing [16], [17]. In addition, recently we have reported that NSSR1 is also highly expressed in reproductive system, indicating the potential roles NSSR1 may play in reproduction [18].…”
Section: Introductionmentioning
confidence: 99%
“…The immunostaining was performed as described previously [15]. The rats were deeply anesthetized with intraperitoneal injection of pentobarbital (40 mg/ml) in accordance with the NIH guidelines for animal experimentation.…”
Section: Immunohistochemical Stainingmentioning
confidence: 99%